(untitled) (Research, Society and Development, 2020)
Bioactive compounds are characterized as secondary metabolites, derived from plants, that exert pharmacological and/or toxicological effects on humans and/or animals. In recent years, such compounds, particularly those exhibiting antioxidant activity, have been employed in the in vitro maturation (IVM) of oocytes from different mammals. Such an application is aimed at increasing the efficiency of in vitro embryo production by reducing the oxidative stress caused by in vitro conditions. This review objective is an overview of the processes of obtaining bioactives and their utilization in the IVM of oocytes by highlighting the different compounds and their roles in reducing the oxidative stress in mammalian oocytes. The review is focused on national and international journals, to gather the best information on the bioguided isolation of compounds that can be utilized in IVM. Generally, the path taken to achieve the final molecule with evident and reproducible activity involves the bioguided and bioprospecting assays with the extraction of the raw material and the studies of its chemical and biological activity. Thus, a series of compounds have already been utilized in cattle, sheep, pigs, and goats, with promising results, compared to those of synthetic antioxidants. The benefit of the bioguided studies, aided by the bioprospecting techniques, is unpredictable in the discovery of bioactive with potential action at the technological level of application. The optimization of these technologies is extremely beneficial to obtaining very evident and reliable results, thus increasing the reproductive success of the species through the large-scale application of the in vitro techniques.